THE STABILTY OF MONEY DEMAND IN INDONESIA: AN ARDL APPROACH - Mahrus Lutfi Adi Kurniawan (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
This study examines the demand for money for both M2 and M1 in Indonesia using the autoregressive distributed lag (ARDL) approach. Based on the results of the bound test, the demand for money in Indonesia is co-integrated, and there is a long-term relationship with factors its determinant namely, income, inflation, domestic interest rates, foreign interest rates and exchange rates. Income, inflation and exchange rate variables have a positive effect on M2 and M1 in the short and long term, while the interest rate variable only affects M2. The stability test using the CUSUM and CUSUMQ approaches found that the demand for money in Indonesia is unstable. The instability in demand for money implies that the money targeting policy in Indonesia cannot be implemented